(untitled) (Revista Brasileira Multidisciplinar, 2022)
The research deepens the discussion of experiences in settlements, to be incorporated into the teaching-learning process. In this respect, the article aims to understand the situation of countryside schools located in rural settlements encompassing education and public policies for the countryside, contributing to the social practice of these schools, considering their specificities. The methodological procedure has sought theoretical basis in the literature of the field, available in the researched scientific databases such as Capes, Scielo, Scopus and Google Scholar, from 2015 to 2020. The Public Policies aimed at the countryside present a broad educational framework and are often city policies adapted to the countryside. For a better understanding of the education that takes place in the countryside as a social practice and still in process of historical constitution, it is necessary the guidance for the relationship between education and public policies.